Laryngotracheal Stenosis: Risk Factors for Tracheostomy Dependence and Dilation Interval. (February 2017) - Gadkaree, Shekhar K.; Pandian, Vinciya; Best, Simon; Motz, Kevin M.; Allen, Clint; Kim, Young; Akst, Lee; Hillel, Alexander T.
Objective: Laryngotracheal stenosis (LTS) is a fibrotic process that narrows the upper airway and has a significant impact on breathing and phonation. Iatrogenic injury from endotracheal and/or tracheostomy tubes is the most common etiology. This study investigates differences in LTS etiologies as they relate to tracheostomy dependence and dilation interval. Study Design: Case series with chart review. Setting: Single-center tertiary care facility. Subjects and Methods: Review of adult patients with LTS was performed between 2004 and 2015. The association of patient demographics, comorbidities, disease etiology, and treatment modalities with patient outcomes was assessed. Multiple logistic regression analysis and Kaplan-Meier analysis were performed to determine factors associated with tracheostomy dependence and time to second procedure, respectively. Results: A total of 262 patients met inclusion criteria. Iatrogenic patients presented with greater stenosis ( P = .023), greater length of stenosis ( P = .004), and stenosis farther from the vocal folds ( P < .001) as compared with other etiologies. Iatrogenic patients were more likely to be African American, use tobacco, and have obstructive sleep apnea, type II diabetes, hypertension, chronic obstructive pulmonary disease, or a history of stroke. Iatrogenic LTS (odds ratio [OR] = 3.1, 95% confidence interval [95% CI] = 1.2-8.2), Cotton-Myer grade 3-4 (OR = 2.6, 95% CI = 1.1-6.4), and lack of intraoperative steroids (OR = 2.9, 95% CI = 1.2-6.9) were associated with tracheostomy dependence. Nonsmokers, patients without tracheostomy, and idiopathic LTS patients had a significantly longer time to second dilation procedure. Conclusion: Iatrogenic LTS presents with a greater disease burden and higher risk of tracheostomy dependence when compared with other etiologies of LTS. Comorbid conditions promoting microvascular injury—including smoking, COPD, and diabetes—were prevalent in the iatrogenic cohort. Changes in hospital practice patterns to promote earlier tracheostomy in high-risk patients could reduce the incidence of LTS.